Successful Treatment of a Case of Metallo-Beta-Lactamase-Producing Raoultella ornithinolytica Bacteremia by Antimicrobial Stewardship Team Intervention and Therapeutic Drug Monitoring-Based Amikacin Treatment - Noriko Koishi; Hiroshi Sasano; Toshihiro Yoshizawa; Mika Shikuri; Hiroshi Matsumoto; Mai Suzuki; Yukiko Fukui; Masayoshi Chonan; Toshimi Kimura; Hirofumi Ichida; Akio Saiura; Toshio Naito (Case Reports in Infectious Diseases)
An 80-year-old woman underwent pancreatoduodenectomy. Post-operation, she experienced a fever, and a culture of blood revealed metallo-beta-lactamase-producing Raoultella ornithinolytica. For treatments with aminoglycoside antimicrobial agents, a therapeutic drug monitoring-based dosing design can lower the risk of adverse events and enable appropriate treatment. Key Clinical Message. When aminoglycoside antimicrobial agents are administered for MBL-producing bacteremia, prescription suggestions based on TDM by antimicrobial stewardship team can reduce the occurrence of adverse events and enable appropriate treatment.